Entre o fogo e as sombras : o papel da magia na literatura nórdica medieval e na obra as crônicas de gelo e fogo, de George R. R. Martin - Barbosa, Thais de Matos (2025)
This doctoral dissertation investigates the presence and function of magic in A Song of Ice and Fire, by George R. R. Martin, in light of magical-religious practices found in medieval Icelandic sagas. Through a comparative and multidisciplinary approach, the study focuses on the character Melisandre, the Red Priestess, analysing how her literary construction echoes Norse traditions, particularly seiðr, galdr, and the feminine figures of völur and seiðkonur. The research draws on primary and secondary sources from Old Norse literature, as well as critical studies on religion, gender, and medievalist fantasy literature. The analysis is structured around five categories of magical manifestations in Melisandre’s actions: prophetic and visionary magic; blood magic and sacrifice; sexual and bodily control magic; creation and summoning magic; and magical immunity and physical resistance. These categories are compared to practices and archetypes from Icelandic sagas, revealing parallels and symbolic transformations. The study also explores magic as a form of symbolic and political power, showing how Melisandre influences the strategic and religious decisions of Stannis Baratheon. Her role reveals the complex entanglement of faith, politics, and the supernatural. Melisandre is interpreted as a contemporary reimagining of the medieval magical woman archetype, embodying power, ambiguity, and agency. This research contributes to the fields of Religious Studies, Literary Studies, and Scandinavian Studies by offering a critical and comparative reading of medieval and modern texts. It emphasizes the academic legitimacy of fantasy literature as a space for complex cultural, symbolic, and political dialogues. Furthermore, it highlights the significance of mystical feminine representations as forms of resistance and narrative transformation. By illuminating the intersections of magic, myth, gender, and power, this dissertation reaffirms fantasy literature as a valuable field of symbolic reinvention and cultural critique.